Mycobacterium spp. exposure, childhood vaccinations, and early childhood brain and CNS cancers - Singh, Samer; Singh, Rakesh K. (Frontiers in Immunology, 2025)
Globally, with improvements in general hygiene, the incidence of early childhood (0-4Y-olds/<5Y-olds) brain and central nervous system (BCNS) cancers is increasing. Although immunological underpinning is suspected, the identification of protective variables for the majority of BCNS cancer cases remains elusive. Extant hypotheses suggest a role for progressively diminishing exposure to common microbes/pathogens in the rise of childhood cancers in industrialized countries with improved hygiene. Natural exposure to common microbes/pathogens and childhood vaccinations help train the developing immune system of children to respond appropriately to future infections and maintain a healthy immune system. Considering the established role of childhood vaccinations in augmenting immunity, including “trained immunity," their protective role in pediatric cancers may be surmised. However, a lack of definitive theoretical and practical frameworks to explain conflicting observations has impaired progress. When we analyze the epidemiological data of European region countries with different childhood vaccination policies but more similar socioeconomic conditions, access to medical services, and genetic makeup as compared to other parts of the world, the coverage of seven major childhood (0-1Y-olds) vaccines does not significantly associate with BCNS cancer incidences in the same cohort of 0-4Y-olds (2020). However, interestingly, prevailing tuberculin immunoreactivity, a surrogate for the existence of heterologous cell-mediated immunity resulting from exposure to Mycobacterium spp., including Bacille Calmette-Guérin (BCG) vaccination, for these populations, is found consistently negatively correlated with the BCNS cancer incidence in 0-4Y-olds for countries mandating neonatal BCG vaccination [r(24): -0.7226, p-value:<0.0001]. Seemingly, neonatal immune-system priming by BCG and boosting by exposure to environmental Mycobacterium spp. appear protective in 0-4Y-olds. Exploration of BCNS cancer incidence and prevailing immune correlates in matched cohorts, along with prospective randomized controlled trials, may be warranted to conclusively ascertain the impact of childhood vaccinations and boosters (including natural exposure) on early childhood BCNS cancer incidence.